Experimental verification of 'waveguide' plasmonics. (6th December 2017) - Prudêncio, Filipa R; Costa, Jorge R; Fernandes, Carlos A; Engheta, Nader; Silveirinha, Mário G
Abstract: Surface plasmons polaritons are collective excitations of an electron gas that occur at an interface between negative- ε and positive- ε media. Here, we report the experimental observation of such surface waves using simple waveguide metamaterials filled only with available positive- ε media at microwave frequencies. In contrast to optical designs, in our setup the propagation length of the surface plasmons can be rather long as low loss conventional dielectrics are chosen to avoid typical losses from negative- ε media. Plasmonic phenomena have potential applications in enhancing light–matter interactions, implementing nanoscale photonic circuits and integrated photonics.